Strategi Pemasaran Angkringan Cak Gembel Manggar Permai Jember dalam Upaya Meningkatkan Minat Beli Konsumen - Atikah, Sifa Zhahrotul Atikah; Wardhani, Roro Aditya Novi; Hapsari, Yusita Titi (Jurnal Manajemen Dayasaing, 2024)
ABSTRACTThis research aims to explore information regarding the role of marketing strategies in dealing with problems at Angkringan Cak Gembel, namely the rise and fall of the number of visitors, which sometimes fluctuates and sometimes decreases. Descriptive qualitative is the method used in research that focuses on interview data, observation, documentation, and questionnaires as primary data and literature studies as secondary data. Angkringan owner Cak Gembel and three employees as research subjects and ten consumers. The questionnaire sample was determined randomly at Angkringan Cak Gembel. SWOT, IFAS, and EFAS analyses produce a deep understanding of the condition of Angkringan Cak Gembel. The findings show that Angkringan Cak Gembel has powerful opportunities, strengthened by opportunities, and the value of strengths far exceeds the value of identified threats and weaknesses. This research not only provides detailed insight into the Angkringan Cak Gembel opportunity but also highlights potential strategies that can be used to increase marketing competitiveness in a broader scope. Thus, research was carried out to determine marketing strategies and consumer buying interest, which could have a positive impact on sales growth. Keywords: Angkringan; SWOT Analysis; Marketing Mix; Marketing Strategy